(3CdZGR MjQJ GdYGdes - (3YHO GdeYR, CMeO YHO GdQMjes; (3GdUHGZ, CMeOs; (3ShGM, SGde YHO GdeYRs ((3GdefhajI, eUQs (3MhGOjJ ddfTQ hGdJhRjYs, 2023)
(3cJGH CdZGR MjQJ GdYGde(B. (3GdeDda(B: (3CMeO YHO GdQMje(B. (3ef GQJcH cd Jdc GdLQGFe GdJj de jYKQhG Ydi LGfj ajgG ? Cjf PgH gDdGA GdCTNGU GdPjf GNJahG hdf jYKQhG dge Ydi CKQ? eGPG JYQa Yf eWGQ OfaQ Ch Yf GdHSJGf GdHhgjej ? eGPG JYQa Yf fXQjI GdeDGeQI hef jDef HgG ? eG gh OhQ GdeGShfjI aj EOGQI GdYGde ? ef jMce GdYGde aj GdNaGA? ef GdeDcO Cfc Sha JZjQ fXQJc Yf GdYGde HYO gPG GdcJGHs
Keywords: (3GdCdZGRs; (3GdZQGFHs